Neurotological findings after electrical injury at the workplace. (24th January 2017) - Wuesthoff, Carolina; Ilan, Ophir; Rutka, John Alexander
Abstract : Objectives/Hypothesis: Neurotological findings secondary to electrical injuries have rarely been reported in the world literature. We attempt to characterize the neurotological findings following electrical injury and to determine the role head injury and loss of consciousness play in this population's clinical presentation. Study Design: Retrospective cohort study. Methods: A database containing 3, 438 patients with work‐related injuries was scanned for individuals who sustained and survived electrical injuries at work. Detailed analysis of the frequencies of presenting features and test results was performed. A comparative analysis was made between the subsets of patients with and without loss of consciousness and/or head injury. Results: A cohort of 42 patients was identified. All patients had multiple symptoms. Dizziness was a significant complaint in all workers with electrical injuries. Other common complaints included tinnitus and imbalance. Characterization of these symptoms is provided in detail according to statistical frequency. In this cohort, 25 workers had a concomitant head injury and 17 workers had an associated loss of consciousness. There was no statistically significant difference when clinical presentation, examination, and balance testing results were compared between the subsets. Conclusions: Frequency and characterization of symptoms following electrical injury are provided. Dizziness is the most common presenting neurotological feature. Loss of consciousness and/or associated head injury do not affect the clinical presentation in this particular population. Level of Evidence: 2b. Laryngoscope, 127:2126–2131, 2017